Transformasi Rasionalitas dan Krisis Subjektivitas dalam Filsafat Barat serta Implikasinya Bagi Pemikiran Kontemporer - Nurhildawati; Ramsiah Tasruddin (Yayasan Al-Afif, 2025)
This article examines the shifting understanding of rationality in Western philosophy from Ancient Greece to postmodern thought and explores its implications for the contemporary conception of human subjectivity. Rationality, which was initially understood as a cosmic order and an ethical orientation, gradually evolved into a foundation for the autonomy of the subject and the legitimation of knowledge in modern philosophy. However, the increasing dominance of instrumental reason within modernity generated new tensions, particularly in relation to the loss of meaning and the weakening of the subject’s position as a coherent center of consciousness. Through a historical and critical reflection on key philosophical traditions and thinkers, this article argues that postmodern critiques of rationality do not simply reject reason itself, but rather expose its limitations in accounting for the complexity of human experience. The crisis of subjectivity in contemporary thought can therefore be understood as the outcome of the long historical transformation of rationality. This study offers a conceptual mapping that opens space for a more reflective and dialogical understanding of rationality in addressing present-day philosophical challenges.